Multidimensional patterning and manipulating of microparticles and cells using surface acoustic waves - Nguyen, Tan Dai (Nanyang Technological University, 2021)
Patterning and manipulating of living cells and microparticles have tremendous potential applications in microfluidics, biology, tissue engineering and material assembling. Among many possible techniques, the technology based on surface acoustic waves (SAWs) has attracted many attentions owing to its good biocompatibility, low-power consumption, autonomy capability, nature of non-invasive and non-contact. SAWs have been proved to present outstanding performance in the manipulation of a single and group of cells or microparticles inside the polydimethylsiloxane (PDMS) microfluidic channels. However, most of SAW microfluidic devices reported so far had two major limitations, 1) the lack of capability of three dimensional (3D) manipulating and patterning; 2) the lack of precise and reliable controls. Those limitations need to be overcome in order to develop an efficient and automated system where the biological cells can be precisely manipulated in three dimensions. Hence, this research aims to investigate and develop the technology for three-dimensional patterning and manipulating of microparticles and cells through advanced design and implementation of a closed-loop control strategy in SAW-based microfluidic devices.